OECMs in marine capture fisheries: Key implementation issues of governance, management, and biodiversity - Serge Michel Garcia; Jake Rice; Amber Himes-Cornell; Kim Jerome Friedman; Anthony Charles; Daniela Diz; Joseph Appiott; Michel J. Kaiser (Frontiers in Marine Science, 2022)
The ‘Other Effective Area-based Conservation Measure’ (OECM) concept was first introduced in 2010, by the Conference of the Parties of the Convention on Biological Diversity (CBD COP) in the CBD Strategic Plan for Biodiversity conservation 2011–2020. The concept acknowledged that a range of spatial measures other than protected areas were appropriate for reaching Aichi Target 11 spatial conservation coverage. The OECM definition was adopted in 2018 in CBD COP Decision 14/8, which calls on States to mainstream OECMs into economic sectors, to recognize the current biodiversity conservation benefits and co-benefits from their area-based management measures and enhance them as much as possible. In the marine capture fisheries sector, the identification of OECMs is a work in progress and the issues addressed in this paper are key implementation issues that States and fisheries authorities are or will be encountering regarding their governance, management, and biodiversity outcomes. The purpose of the paper is to draw attention to some key OECM implementation issues arising in marine capture fisheries and to suggest possible approaches to address them. The governance issues addressed relate to enabling frameworks, industrial fisheries, legitimate authorities, long-term commitments, cross-sectoral coordination and planning, and contribution to the Post-2020 Global Biodiversity Framework of the CBD. The management issues considered relate to effectiveness in achieving expected outcomes, costs and benefits of OECMs, spatial relations between OECMs and fisheries, and the role of OECMs in the Ecosystem Approach to Fisheries (EAF). Regarding the significant positive biodiversity outcomes expected from OECMs, issues relate to the type of outcomes expected, their current or intended nature, the level of evidence required, and their relationship to area-based conservation standards.